ANTONI MESSING, WSPÓŁTWÓRCA POMNIKA NAJŚWIĘTSZEJ MARYI PANNY PRZED KOŚCIOŁEM REFORMATÓW I SERII WZOROWANYCH NA NIM NAGROBKÓW WZNIESIONYCH NA CMENTARZACH WARSZAWY - Wiraszka, Marta (Saeculum Christianum. Pismo Historyczne, 2017)
Antoni Messing (ca. 1821-1867) the owner of the stone workshop located in Warsaw on 6 Powązkowska Street (mtge. 27C) is currently most famous for one monument- the Statue of the Virgin Mary of Immaculate Conception which was placed in front of the Church of St Antony of Padua on Senatorska Street (1851). What made this monument different from other independently standing monuments was the use of lanterns which at evening time illuminated the statue of the Virgin (1853). The innovative idea spread not only around Warsaw, but also outside the city boundaries. References to the monument elevated by Messing were not limited to the way and form of illuminating the statue. The inventory research conducted on Warsaw cemeteries enable the extraction of a group of tombstones imitating the shape and the decor of the plinth of the statue of the Virgin. The number of examples of this collection of tombstones numbers 19. Their execution dates back to the period 1853-1874 - with one exception only, all of them were elevated during the period of Antoni Messing’s ownership of the stone workshop. All of them represent the same commemoration in the form of a crucifix located on a plinth. Examples can be separated into two groups. One, comprising 8 tombstones, the closest to the original, the other, comprising 11 examples preserves the architectural structure without the sculptural decor. The origin of the formal concept is to be traced in the project of Henryk Marconi’s garden vase designed for Wilanowski Park (ca. 1845-1851) as well as the finishing elements of the Stanisław and Antoni Potocki’s tombstones. Consequently, the contribution of Messing consists in the creation of the series of tombstones modeled on the statue of the Virgin Mary rather than the originality of the project.